2018
DOI: 10.1002/spy2.23
|View full text |Cite
|
Sign up to set email alerts
|

The Internet of Things and the Smart City: Legal challenges with digital forensics, privacy, and security

Abstract: The explosive growth of information and communications technologies (ICTs) as manifested in Smart Cities and the Internet of Things (IoT) creates more and more computable data with myriad benefits. They also produce ever more digital evidence of people's lives in all contexts, with commensurately greater potential risks to the safety and rights of citizens. Digital/computational forensics and analytics, used to combat crime, are the vanguard of the collision of these with public policy as to privacy and person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 17 publications
0
33
0
2
Order By: Relevance
“…Hence, encryption represents a "trade-off" between the success of the investigation and citizen privacy rights [91]. Losavio et al [103] concludes that maintaining that balance between the needs of the state and the needs of the citizens will play a central role in the future of the forensic discipline.…”
Section: B Evidence Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, encryption represents a "trade-off" between the success of the investigation and citizen privacy rights [91]. Losavio et al [103] concludes that maintaining that balance between the needs of the state and the needs of the citizens will play a central role in the future of the forensic discipline.…”
Section: B Evidence Acquisitionmentioning
confidence: 99%
“…4) Legal Issues: Losavio et al [103], provide an overview of present and future legal concerns in relation to IoT security and forensics. One of the main points refers to the conflicting legal guidance in case of cross-border crimes, including the absence of clear procedural and contractual agreements.…”
Section: Evidence Analysis and Correlationmentioning
confidence: 99%
“…The Uniform Commercial Secrets Act also defines trade secrets: "Information including a formula, pattern, composition, program, device, method, technique, or process whose first, economic, actual or potential value This results from the fact that no one is generally known and is not readily available to other persons who can gain economic benefit by disclosing or using it. Secondly, conventional efforts have been made to keep it secret (LOSAVIO, 2018).…”
Section: Digital Forensicsmentioning
confidence: 99%
“…The researchers in [20] employed neural networking techniques for evaluating DoS invasions. Its experiments revealed that the neural networking approaches senses the DoS invasions with great precision and accuracy compared to any other method.…”
Section: Application Of Ann (Artificial Neuralmentioning
confidence: 99%